Diagnosis And Treatment Of Pseudopregnancy In A Non-Descriptive Doe - Arunmozhi, N.; Gopikrishnan , D.; Sathiamoorthy , T.; Rangasamy, S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Pseudopregnancy in goats occurs usually after mating or post-oestrus without breeding or early embryonic death with persistent corpus luteum (Moraes et al., 2007). The life span of corpus luteum (CL) is determined by the luteotrophic and luteolytic mechanisms. A disturbance in any one of the mechanisms may be the underlying cause of the persistent luteal function in case of pseudopregnancy. Furthermore, the persistence of luteal function which was associated with plasma progesterone level, higher than 2 ng/ml; induced fluid accumulation in the uterus (Kornalijnslijper et al., 1997a). The increased life span of CL in pseudopregnant goats reflects the absence of acute luteolytic signal of uterine origin (Currie et al., 1988). The levels of progesterone in the plasma at the start and during the course of pseudopregnancy seemed to be influenced by the intrauterine events. The levels of plasma progesterone in pseudopregnant goats were lower than those in pregnant goats from the very beginning of the luteal phase, indicating less luteotrophic support, because of the absence of conceptus (Kornalijnslijper et al., 1997b). The spontaneous resolution of pregnancy did not eliminate all the uterine fluid and that the remaining fluid may be responsible for the recurrence of pseudopregnancy by preventing luteolysis (Lopes et al., 2001).